Audit Sistem Informasi Absensi Pada MI Miftahul Ulum Menggunakan Cobit 4.1 - M. Irfandi; Eva Zuraidah (Journal of Informatics Management and Information Technology, 2022)
This study aims to determine the extent to which the company implement IT governance. The focus of this research is on the COBIT 4.1 domain, namely PO1, PO4, PO9, DS5, DS9, DS12, and ME. The method is based on COBIT 4.1, this research uses several stages, namely literature review, data collection, and data processing at MI Miftahul Ulum. The results of data processing are used to find weaknesses in each domain. Weaknesses or problems compared to the ideal conditions that have been set for the COBIT 4.1 audit framework at each level, the problem encountered at MI Miftahul Ulum is that there are still problems with the attendance system, problems often occur such as not being read by the system even though they have made attendance which results in reduced attendance. teacher appraisals and salaries. The results of the calculation of the largest maturity level in the DS12 domain with a maturity level value of 3.89, must be increased again, while the smallest value in the PO1 domain with a maturity level value of 3.15 must be repaired again so that the attendance system is as expected.